Enhancing the Tribological Behavior of Hybrid Al6061 Metal Matrix Composites through the incorporation of Nickel and Chromium Nanoparticles - Kumar, Raj; Shringi, Dr. Dinesh; Bairwa, Kedar Narayan (International Journal of Advanced Engineering, Management and Science, 2020)
In this work, the influence of addition of nickel and chromium micron/nano particles on the tribological behavior of developed Al6061 hybrid metal matrix composites has been identified. In the first category Al6061 based hybrid metal matrix composite reinforced with x wt.% of nickel (x=0, 0.9, 1.8 and 2.7) and same wt.% of chromium micron size particles were fabricated throughcost- effective stir casting technique. In the second category Al6061 based hybrid nano metal matrix composites reinforced with y wt.% of nickel(y=0, 0.6 and 1.2) and same wt.% of chromium nanoparticles developed through same technique. Graphite and magnesium micron/nano size particles added to improve self-lubrication property and wettability respectively. The wear rate of developed composites has been tested on pin-on-disc experimental set up at defined speed 500 RPM, sliding distance 1000 m and variable load 10N, 20N & 30N. The reduction of wear rate of Al6061/1.8Ni/1.8Cr hybrid metal matrix composite and Al6061/0.6Ninp/0.6Crnp hybrid nano metal matrix composite 37.1% and 76% w.r.to Al6061 alloy. The results revealed that there is significant improvement in wear resistance or decrement in wear rate of hybrid nano metal matrix compositesas compared to hybrid metal matrix composite and Al6061 alloy. An attempt made in this work to provide information for superior tribological behavior of hybrid nano metal matrix composites.